Relationship between balance performance and leg muscle strength in elite and non-elite junior speed skaters - Akahane, K.; Kimura, T.; Cheng, G. A.; Fujiwara, T.; Yamamoto, I.; Hachimori, A. (Journal of Physical Therapy Science, 2006)
The purpose of the present study was to examine the relationship between balance performance during one-leg and two-leg standing and leg muscular strength in junior speed skaters, and to formulate one indicator for on-land training. There were a total of 48 subjects comprising 22 junior elite and 26 junior non-elite speed skaters. The method involved analyzing the unit trajectory length (LNG/TIME), the peak value for center of gravity fluctuations (RMS) and the area where fluctuations in the center of gravity are concentrated (SD-A) in keeping one-leg and two-leg standing; and measuring the maximum isometric muscular strength for knee extension with a leg muscular strength measurement device, and thereby calculating a weight-bearing index (WBI). As far as the characteristics for the center of gravity were concerned, significantly lower values in the elite group compared with the non-elite group were exhibited for the peak center of gravity fluctuations (RMS) and the area in which fluctuations in the center of gravity were concentrated (SD-A). However, no significant differences were observed in the unit trajectory length (LNG/TIME). In addition, no significant differences between the groups were observed when the right leg was kept standing. The elite group exhibited significantly higher values in the weight-bearing index (WBI) compared with the non-elite group for both legs. With regards to the differences between the left and right leg WBI, the elite group exhibited significantly higher values for the left leg than the right leg, but no significant difference was observed between left and right in the non-elite group. Based on this, it is suggested that there is a need to carry out qualitative training for improving the ability to keep the left leg standing in a posture simulating skating, and to carry out quantitative training for increasing the muscle strength of knee extensors, in order to improve the competitiveness of junior speed skaters.